High cytotoxic and apoptotic effects of platinum(ii) complexes bearing the 4-acridinol ligand. (12th November 2020) - Shao, Tai-Ming; Wei, Zu-Zhuang; Luo, Xiao-Ling; Qin, Qi-Pin; Tan, Ming-Xiong; Zeng, Jia-Jing; Liang, Chun-Jie; Liang, Hong
Abstract : 4-Acridinol platinum(ii ) complex PtA induces SK-OV-3/DDP cell apoptosis that is mediated by the mitochondrial dysfunction pathway. Abstract : Here, two platinum(ii ) complexes, namely [Pt II (Q)(DMSO)Cl] (PtQ ) and [Pt II (A)(DMSO)Cl] (PtA ), bearing 8-hydroxyquinoline (HQ) and 4-acridinol (HA) ligands were synthesized for the first time and fully characterized by elemental analysis, NMR and IR spectroscopies, and X-ray crystallography. The two 4-acridinol Pt complexes (PtQ and PtA ) were active against cisplatin-resistant SK-OV-3/DDP cancer cells with lower IC50 values than cisplatin. Notably, complex PtA exhibited IC50 values (0.05 ± 0.02 μM) that were an order of two and three magnitude lower than those of the 8-hydroxyquinoline Pt complex PtQ (5.08 ± 0.47 μM) and clinical cisplatin (71.23 ± 1.02 μM), respectively. Interestingly, complex PtA displayed potent cytotoxic activity particularly in cisplatin-resistant SK-OV-3/DDP cells, but it was practically inactive against the human liver HL-7702 normal cells. Analyzing the uptake and distribution of complex PtA in the cisplatin-resistant SK-OV-3/DDP cells revealed that PtA was mainly localized in the mitochondria. In addition, complex PtA significantly caused the loss of bcl-2 and mitochondrial membrane potential (Δ Ψ m ), increase in [Ca 2+ ] and the reactive oxygen species (ROS) levels, cytochrome C (cyto C ), apaf-1, and caspase-3/9 ratio in cisplatin-resistant SK-OV-3/DDP cells. Complex PtA may trigger cell apoptosis via a mitochondrial dysfunction pathway, whereas 8-hydroxyquinoline Pt complex PtQ does not. The better cytotoxicity and the more significant anticancer mechanism of complex PtA than 8-hydroxyquinoline Pt complex PtQ should be undoubtedly correlated with the key roles of the more extended planar 4-acridinol (HA) ligand.